Photodiodes From Fundamentals to Applications - Yun, Ilgu (IntechOpen, 2012)
This book represents recent progress and development of the photodiodes including the fundamental reviews and the specific applications developed by the authors themselves. The key idea of this book is that it allows authors to deal with a wide range of backgrounds and research progresses in photodiode-related areas. With respect to the original collection of the book chapters, this book contains several improvements and new problems and related solutions are also discussed in the areas from fundamental physics and design to device and circuit applications. The book is intended for graduate students, engineers, and researchers who are especially interested in the area of optoelectronic device applications, including photodiodes, solar cells, CMOS image sensors, Optoelectronic Integrated Circuits, etc.